Screening for Resistance and Management of Root-Knot Nematode, Meloidogyne incognita on Bt Cotton (Indian Journal of Nematology, 2024)
Based on 1-5 root knot index, 38 Bt cotton hybrids showed either susceptible or highly susceptible reaction and two were moderately resistant. Highest (39.5%) increase in yield of Mahico 60-25 Bt hybrid over untreated check and significantly lowest final nematode population in the soil was recorded in the treatment combination of a rhizobacterium, Gluconacetobacter diazotrophicus strain 35-47 as seed treatment + carbofuran @ 1.0 kg a.i /ha as soil application followed by 29.3% in seed treatment with carbosulfan @ 3.0% w/w + soil application of carbofuran @ 1.0 kg a.i /ha.